Research on Financing Mechanism of Long-Term Care Insurance in Xiamen, China: A System Dynamics Simulation - Zhang, Liangwen; Fu, Sijia; Fang, Ya (Frontiers in Public Health, 2021)
Objective: This study aimed to predict the changing trend of long-term care insurance (LTCI) funds by clarifying the linkage between revenue and expenditure and its influencing factors and to provide evidence for the establishment of a sustainable LTCI financing mechanism in China. Method: We have taken Xiamen as an example, based on the data from Xiamen Special Economic Zone Yearbook and field survey. The changing trend of LTCI funds is predicted from 2020 to 2030 based on the system dynamics model (SDM) of the LTCI financing system. Also, through literature research and expert consultation, we found the intervention goals and analyzed their impact on the balance of LTCI funds. Results: In the current situation, according to the forecast, the revenue and the expenditure of the LTCI funds will increase year by year from 2020 to 2030 in Xiamen, an increase of about 3.7 times and 8.8 times, respectively. After 2029, the expenditure will exceed the revenue of the LTCI funds and the balance will turn into a deficit. From the perspective of fund revenue, by adjusting the individual payment rate, government financial subsidies, and enterprise payment rate, the proportion of LTCI funds can be increased to alleviate the balance deficit under the original forecast. On the contrary, from the perspective of fund expenditure, increasing the proportion of reimbursement and the rate of severe disability will lead to an increase in fund expenditure. In this case, the balance of the funds will turn into a deficit, 7 years in advance. In addition, it was found that the severe disability rate has the greatest impact on the balance of funds. Discussion: The SDM can objectively reflect the structure and the behavior of the LTCI financing system and has good applicability. By increasing the individual payment rate, government financial subsidies, and enterprise contribution rate, reasonable setting of the reimbursement ratio of nursing services, especially for the prevention of disability among the elderly, to maintain the sustainability of the funds. This study provides strong evidence for policymakers to establish a sustainable LTCI system in China.